Anatomical investigation of four taxa of Scutellaria albida L. (Lamiaceae) (Bangladesh Journal of Plant Taxonomy, 2019)
The root, trunk and leaf anatomy of four taxa of Scutellaria albida namely, S. albida subsp. albida, S. albida subsp. velenovskyi, S. albida subsp. colchica and S. albida subsp. condensata were examined. The aim is to determine whether these characters can be used for systematic purposes. The roots displays a typical stele structure in all studied taxa. But their number of pith rays are different in each taxa. The stems of S. albida taxa have square like transection, collateral vascular bundles, parenchymatous pith and show 1-2 layered epidermis coated with thick cuticle. S. albida subsp. condensata has papillate epicuticular wax on its stem cuticle layer. In all taxa angular collenchyma, and cambium forming phloem outward and xylem inward are observed. The leaves are hypostomatic, have single rowed epidermis coated with thick cuticle and show dorsiventral mesophyll in all studied taxa. S. albida subsp. velenovskyi has echinate epicuticular wax on its leaf cuticle layer, but the others have smooth cuticle layer. The midrib shows one collateral bundles in all taxa but the shape of median veins of the leaf blade show variation in each taxa. Some of the anatomical characters viz. the number of pith rays of roots, the number of palisade parenchyma layer, plant cuticles covered by wax, the shape of median veins of the leaf blade and stomata index, provide information of taxonomical significance for these taxa.